THE MODELS OF CHANGING AND GIVING INFORMATION IN INTEGRATED INFORMATIONAL-ANALYTICAL SYSTEMS - Professor Zaripov Oripjon Olimovich; PhD Khamrakulov Umidjon Sharabidinovich (International Journal of Innovations in Engineering Research and Technology, 2021)
The problems were looked through in this article on working out the mathematic models of the algorithms of changing and giving information in integrated informational-analytical systems. It is worked out the mathematic models of mutual connectional components by the help of connectional functions of informational systems. Besides that, here given the structure of organization the generalized components of informational-analytical system.